Biomimicry and the Problem of Praxis. (1st October 2019) - Mathews, Freya
Biomimicry can serve as a design template for an ecological civilisation by showing how cyclical, no-waste, mutually adaptive production systems designed 'after nature' could render human industry fully 'sustainable'. However, unless the modes of praxis involved in such a reformed industrial base are also redesigned, the value orientation fostered by the new order would remain anthropocentric. Biomimicry would accordingly result in an eco-modernist-type scenario in which society was 'decoupled' from nature, with dystopian consequences for the larger community of life. Drawing on Indigenous modalities, I explore ways in which modern industrial systems could include participatory modes of praxis that would emanate in genuinely bio-inclusive forms of consciousness and hence lay the ethical foundations for an ecological civilisation.